2021
DOI: 10.3390/agronomy11050883
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Fertilization Regimes on Yield, Selected Nutrients, and Bioactive Compounds Profiles of Onion

Abstract: Here we report the results of a three-year replicated field trial on the effects of novel clover- and alfalfa-based fertilizer products (Ekofert® K and Ekofert® L), with the input levels equivalent to 120, 180, or 240 kg N ha−1, on the yield and selected sensory and nutritional quality parameters of onion. The study showed that Ekofert fertilizer applied at all three levels produced similar or higher yields than the standard fertilization regimes used in conventional farming in all three seasons. Significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
4
11
0
Order By: Relevance
“…Additionally, in 2022, higher levels of humus, N, and P were measured compared to the soil in 2021 (Table 1), further explaining the significantly higher yield in 2022. The strong impact of the year of harvest was also noted by Kazimierczak et al [69], where onion yield in 2012 was 75.8 t/ha, and in the following year, 2013, it decreased to 38.7 t/ha.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, in 2022, higher levels of humus, N, and P were measured compared to the soil in 2021 (Table 1), further explaining the significantly higher yield in 2022. The strong impact of the year of harvest was also noted by Kazimierczak et al [69], where onion yield in 2012 was 75.8 t/ha, and in the following year, 2013, it decreased to 38.7 t/ha.…”
Section: Discussionsupporting
confidence: 62%
“…Sulfoxide compounds are responsible for the flavor and aroma of onions [31]. Different fertilization regimes have previously been shown to influence the onion flavor profile [32]. As an example, Coolong and Randle [14] demonstrated that N availability directly influenced the levels of S-methyl-L-cysteine sulfoxide, a precursor of pyruvic acid in freshly cut short-day onions, which authors suggested might affect flavor quality in the bulb.…”
Section: Discussionmentioning
confidence: 99%
“…The crop doesn't require a lot of water compared to other arable crops but has high nutrient demand particularly nitrogen, phosphorus and potassium. According to research carried in several parts of the world by Gateri et al (2018); Gererufael et al (2020); Kazimierczak et al (2021); Yoldas et al (2011) adequate levels of nitrogen (N), phosphorous (P), potassium (K) significantly increases seed survival, plant height, number of leaves, leaf length, average bulb weight, bulb diameter, total and marketable yield as well as quality. The crop Ranks as the third most important vegetable in Kenya after brassicas and tomatoes (MOA, 2004).…”
Section: Introductionmentioning
confidence: 99%